The association between Internet use and cognitive ability among rural left-behind children in China - Gao, Ai-zhi; Chen, Wei-chao (Frontiers in Public Health, 2024)
Introduction: This study focuses on the cognitive development of rural children aged 10-15 who have been left behind, utilizing data from the China Family Panel Studies (CFPS) datasets of 2016 and 2020. The primary objective is to investigate the correlation between Internet usage and the cognitive ability of these children. Methods: An Ordinary Least Squares (OLS) regression model was initially employed to explore the potential influence of Internet use on the cognitive ability of rural left-behind children. To meticulously address potential endogeneity, we employed the instrumental variable (IV) method. Additionally, we performed robustness checks using Propensity Score Matching (PSM) to ensure the reliability of our findings. Results: The findings indicate a statistically significant positive correlation between Internet usage and the cognitive ability of left-behind rural children. Notably, the impact of Internet use is more pronounced in girls than in boys among this demographic. Furthermore, a significant influence of Internet usage on the cognitive ability is observed in rural children aged 10-12, whereas no significant correlation is found for those aged 13-15. Particularly noteworthy is the substantial impact of Internet use on the cognitive ability of left-behind children with an absent father. In addition, the cognitive benefits associated with Internet use were notably more pronounced among rural left-behind children, especially when considering factors such as attendance at a demonstration school and parental concern for the child's education. Conclusion: This study underscores the importance of understanding the relationship between Internet usage and cognitive development in left-behind rural children. These findings highlight the need for targeted interventions and inclusive access to online resources for the development of rural left-behind children.